Brain drain: Do economic conditions “push” doctors out of developing countries? - Okeke, Edward N. (Social science & medicine (1982), 2013)
Health worker migration is an issue of first order concern in global health policy circles and continues to be the subject of much policy debate. In this paper, we contribute to the discussion by studying the impact of economic conditions on the migration of physicians from developing countries. To our knowledge, this is one of the first papers to do so. A major contribution of this paper is the introduction of a new panel dataset on migration to the US and the UK from 31 sub-Saharan Africa countries. The data spans the period 1975–2004. Using this data, we estimate the impact of changes in economic conditions on physician migration. In our preferred specification that allows for country-specific time trends, we find that a temporary one percentage point decline in GDP per capita increases physician migration in the next period by approximately. 3 percent. In our IV models a one percentage point decline in GDP per capita increases physician migration in the next period by between 3.4 and 3.6 percent. Overall, our results suggest a significant effect of developing country economic conditions on physician migration. •We study the effect of economic conditions on migration of health professionals.•We analyze data on physician migration from 31 African countries from 1975 to 2004.•We find a strong counter-cyclical effect of economic growth on physician migration.